A little frog leaps a long way: compounded colonizations of the Indian Subcontinent discovered in the tiny Oriental frog genus Microhyla (Amphibia: Microhylidae) - Gorin, Vladislav A.; Solovyeva, Evgeniya N.; Hasan, Mahmudul; Okamiya, Hisanori; Karunarathna, D.M.S. Suranjan; Pawangkhanant, Parinya; Silva, Anslem de; Juthong, Watinee; Milto, Konstantin D.; Nguyen, Luan Thanh; Suwannapoom, Chatmongkon; Haas, Alexander; et al. (Creative Commons CC-BY 4.0, 2020)
Frogs of the genus Microhyla include some of the world’s smallest amphibians and represent the largest radiation of Asian microhylids, currently encompassing 50 species, distributed across the Oriental biogeographic region. The genus Microhyla remains one of the taxonomically most challenging groups of Asian frogs and was found to be paraphyletic with respect to large-sized fossorial Glyphoglossus. In this study we present a time-calibrated phylogeny for frogs in the genus Microhyla, and discuss taxonomy, historical biogeography, and morphological evolution of these frogs. Our updated phylogeny of the genus with nearly complete taxon sampling includes 48 nominal Microhyla species and several undescribed candidate species. Phylogenetic analyses of 3,207 bp of combined mtDNA and nuDNA data recovered three well-supported groups: the Glyphoglossus clade, Southeast Asian Microhyla II clade (includes M. annectens species group), and a diverse Microhyla I clade including all other species. Within the largest major clade of Microhyla are seven well-supported subclades that we identify as the M. achatina, M. ﬁssipes, M. berdmorei, M.superciliaris, M.ornata, M.butleri, and M.palmipes species groups. The phylogenetic position of 12 poorly known Microhyla species is clariﬁed for the ﬁrst time. These phylogenetic results, along with molecular clock and ancestral area analyses, show the Microhyla—Glyphoglossus assemblage to have originated in Southeast Asia in the middle Eocene just after the ﬁrst hypothesized land connections between the Indian Plate and the Asian mainland. While Glyphoglossus and Microhyla II remained within their ancestral ranges, Microhyla I expanded its distribution generally east to west, colonizing and diversifying through the Cenozoic. The Indian Subcontinent was colonized by members of ﬁve Microhyla species groups independently, starting with the end Oligocene—early Miocene that coincides with an onset of seasonally dry climates in South Asia. Body size evolution modeling suggests that four groups of Microhyla have independently achieved extreme miniaturization with adult body size below 15 mm. Three of the ﬁve smallest Microhyla species are obligate phytotelm-breeders and we argue that their peculiar reproductive biology maybe a factor involved in miniaturization. Body size increases in Microhyla—Glyphoglossus seem to be associated with a burrowing adaptation to seasonally dry habitats. Species delimitation analyses suggest avast underestimation of species richness and diversity in Microhyla and reveal 15–33 undescribed species. We revalidate M. nepenthicola, synonymize M. pulverata with M. marmorata, and provide insights on taxonomic statuses of a number of poorly known species. Further integrative studies, combining evidence from phylogeny, morphology, advertisement calls, and behavior will result in a better systematic understanding of this morphologically cryptic radiation of Asian frogs.